Juxta Cortical Tibia Metastatic Deposition in Gastric Cancer: A Case Report - Majid Sajjadi Saravi; M. Hossein Karimi Nasab; Masoud Shayeste Azar; Ghasem Janbabai; Mehrdad Taghipour; S. Omid Emadian Saravi; Fariborz Eshghi (Case Reports in Medicine)
We report a 41 years old man with rapidly growing and tender lump on the anteromedial surface of tibia. The patient had the history of gastrectomy and gastrojejunostomy due to gastric carcinoma. On admission, the Simple X-ray of lower extremity disclosed a slight thinning of the anterior cortex of tibia without cortical destruction. The whole-body bone scan with 99mTC MDP revealed activity of lesion in all 3 phases. The histopathological evaluation showed an infiltration of bone with tumor cells. Review No the literature revealed in previous cases of skeletal metastasis from gastric cancer in the tibia like this.